Potensi Ekstrak Daun Picung (Pangium edule) sebagai Bahan Pemingsan Ikan Nila (Oreochromis niloticus) pada Transportasi Sistem Kering - Aris Munandar; Forcep Rio Indaryanto; Hana Nurullita Prestisia; Novi Muhdani (Universitas Sriwijaya, 2017)
Consumer demand for live fish commodities has increased, especially for the type of fish that have high economic value, one of which is tilapia (Oreochromis niloticus). Good handling transportation system is needed to make fish still alive until destination. The purpose of this research is to determine the concentration of Pangium edule leaves extract best as the fainting of tilapia in fish transportation. This research method was an experiment with two replications with each concentration 0, 600, 800, 1000, 1300, 1700 and 2500 ppm. The research consists of a preliminary research to determine the limited concentration extract of Pangium edule leaves that can make mortality to the fish and primary research to determine effective concentration as anesthetic material and application during dry transportation system. The results showed that the effective concentration of Pangium edule leaves was 2500 ppm with faint average 35 minutes and recovery time was 5 minutes. Application of Pangium edule leaves extract for the dry transportation system with a concentration of 2500 ppm reached an optimum level of survival rate was 100% for 2 hours.